Answer:
The standard form of the equation is 2x + 5y = -1
Step-by-step explanation:
To find this equation in standard form, we first need to find the slope of the line. We can do that by using the slope formula with the two points.
m(slope) = (y2 - y1)/(x2 - x1)
m = (1 - -3)/(-3 - 7)
m = 4/-10
m = -2/5
Now that we have the slope, we can use that along with the point in point-slope form
y - y1 = m(x - x1)
y - 1 = -2/5(x + 3)
Now that we have that, we can solve for the constant and rationalize the denominators.
y - 1 = -2/5x - 6/5
2/5x + y - 1 = -6/5
2/5x + y = -1/5
2x + 5y = -1